2021
DOI: 10.1091/mbc.e19-10-0568
|View full text |Cite
|
Sign up to set email alerts
|

Spatial proximity of proteins surrounding zyxin under force-bearing conditions

Abstract: Sensing physical forces is a critical first-step in mechano-transduction of cells. Zyxin, a LIM domain-containing protein, is recruited to force-bearing actin filaments and is thought to repair and strengthen them. Yet, the precise force-induced protein interactions surrounding zyxin remain unclear. Using Biotin IDentification (BioID) analysis, we identified proximal proteins surrounding zyxin under normal and force-bearing conditions by label-free mass spectrometry analysis. Under force-bearing conditions, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Zyxin's N-terminus contains one binding site for the dimeric actin crosslinker a-actinin [66,67] and four binding sites for the tetrameric actin polymerization factor Ena/VASP [68,69]. While direct binding interactions between these proteins have been observed biochemically, the precise mechanism for coordinating SF repair remains unknown [58,[66][67][68][69]. A recent study reported that VASP promotes actin assembly by forming multivalent clusters on actin filaments with lamellipodin, a partner which features tandem VASP-binding sites similar to zyxin's [70].…”
Section: Mechanically Switched Abps As Initiators Of Mechanotransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zyxin's N-terminus contains one binding site for the dimeric actin crosslinker a-actinin [66,67] and four binding sites for the tetrameric actin polymerization factor Ena/VASP [68,69]. While direct binding interactions between these proteins have been observed biochemically, the precise mechanism for coordinating SF repair remains unknown [58,[66][67][68][69]. A recent study reported that VASP promotes actin assembly by forming multivalent clusters on actin filaments with lamellipodin, a partner which features tandem VASP-binding sites similar to zyxin's [70].…”
Section: Mechanically Switched Abps As Initiators Of Mechanotransductionmentioning
confidence: 99%
“…1B). Within the cytoplasm, proteomics studies have revealed many LIM proteins to be enriched in stress fibres and focal adhesions in the presence of myosin activity [9–11,58]. Nuclear localization of several superfamily members has also independently been reported, where they have been suggested to regulate gene expression as transcriptional co‐activators [59].…”
Section: Introductionmentioning
confidence: 99%
“…Biotinylation and biotin/streptavidin affinity techniques are essential biosensing tools [ 40 , 41 ] in proteomics [ 40 , 42 ]. Proximity-dependent biotin identification (BioID) is a powerful tool to identify novel protein–protein and proximity-based interactions in living cells [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these multiprotein complexes, there are several proteins present with FPPPP-motifs to recruit VASP ( Renfranz and Beckerle, 2002 ). Zyxin ( Hoffman et al., 2006 ; Cheah et al., 2021 ), palladin ( Gateva et al., 2014 ), and vinculin ( Reinhard et al., 1996 ) are all situated at the actin-regulating area in the focal adhesion complex and can localize VASP to the forming actin filaments at the adhesion sites ( Kanchanawong et al., 2010 ). Therefore VASP can in biological systems be recruited by multiple different proteins from the cytosol toward the membrane to exert its function on actin.…”
Section: Introductionmentioning
confidence: 99%